Empire Juridic Analysis in Coconut Plantation Land Dispute Case - Nuriyanti Santili (Estudiante Law Journal, 2022)
The purpose of this study was to find out how the empirical juridical analysis of coconut plantation disputes in botutonuo village. This study uses a type of empirical juridical research, which places facts in the field as the main data in the study. Sources of data used are primary data as the main data (the results of observations, field interviews, and documentation), and secondary data such as books, laws, regulations, and scientific works. While the population and samples used are the Botutonuo Village Office, the parties involved, the community, and the Botutonuo Village government. The results show that the empirical juridical analysis of coconut plantation disputes in botutonuo village is that the judge in deciding this dispute was correct based on the facts revealed in court by deciding that the defendants were found guilty of controlling the object of the dispute unilaterally and had sold it to someone else and the cause of the dispute. Coconut plantations in botutonuo village are caused by the pattern of responding to inheritance law regulations and secondly supporting factors such as the greed of the disputing parties, not distributing the inheritance immediately, and the lack of good faith.